Measuring Performance Using Swot Analysis and Balanced Scorecard - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L (Elsevier B.V., 2019)
This paper presents a method to measure the performance of a company by combining Strengths-Weakness-Opportunities-Threats Analysis (SWOT analysis) and the Balanced Scorecard (BSC) through the Analytical Network Process (ANP). BSC is a strategic measurement system that has become a strategic management system. A BSC includes strategic objectives and performance indicators that are aligned with the mission and strategy of the organization. The literature in modeling a BSC using Multicriteria Decision Making Methods (MCDM) is vast. Methods such as ANP have been used for different purposes. On the other hand, Strengths-Weaknesses-Opportunities and Threats Analysis (SWOT) analysis is a methodology for analyzing a company from an internal and external perspective in order to generate strategies for the firm. It has also been modeled quantitatively in order to produce strategies. This paper presents a method that combines quantitatively BSC and SWOT analysis to assess a company. The proposed method was implemented in a company that belongs to the food industry. After the application, managers were asked about the method and the implementation process. They found that the method was useful., but time consuming. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0/)